Gilles Paquet : homo hereticus - Andrew, Caroline, 1942-; Paquet, Gilles; Roy, Jeffrey; Hubbard, Ruth, 1942- (Governance series (Ottawa, Ont.), 2009)
This volume explores and contextualizes the contributions of Gilles Paquet as a social scientist. A quintessential public intellectual, Gilles Paquet's long and multifaceted career has shown him to be a thinker of significant power and creativity. This self-described "homo hereticus"--Always critical and sometimes controversial--has influenced scholars and policy makers in Canada and around the globe. The contributors reveal how his assessments of economics, politics, public administration, and education have stirred their minds and helped them make sense of the world around them. T